DEGENERATIVE ENCEPHALOPATHY ASSOCIATED WITH SENILITY IN AN ELDERLY DOG: A CASE REPORT - Pessoa Rodrigues, Ayla; Wallison Diniz da Silva, Iacoan; Camila Barros da Silva, Raíssa; Cherles Coral Rodrigues, Beto (Journal of Interdisciplinary Debates, 2025)
Aging in dogs is associated with morphofunctional changes in the central nervous system (CNS), including cortical atrophy, neuronal loss, and the accumulation of pigments such as lipofuscin, similar to those observed in human neurodegenerative diseases. Among these conditions, Canine Cognitive Dysfunction Syndrome (CCDS) and senile brain degeneration stand out as frequent causes of neurological disorders in geriatric dogs. This paper reports the case of a male, mixed-breed dog, approximately 16 years old, that presented with progressive disorientation, ataxia, seizures, and behavioral changes. Given the clinical deterioration and lack of a favorable prognosis, humane euthanasia was chosen, followed by necropsy for diagnostic confirmation. Macroscopic and histopathological evaluation revealed diffuse cortical atrophy, white matter rarefaction, and reactive gliosis, consistent with advanced senile brain degeneration. This case reinforces the importance of necropsy as an essential tool for the differential diagnosis between degenerative, neoplastic, and vascular processes, especially in older dogs with chronic neurological manifestations. Furthermore, it highlights the educational and scientific role of post-mortem examination in veterinary practice, contributing to the improvement of knowledge about degenerative encephalopathies and to ethical decision-making based on animal welfare.